Resting Energy Expenditure in Anorexia Nervosa: Measured versus Estimated. (18th September 2011) - El Ghoch, Marwan; Alberti, Marta; Capelli, Carlo; Calugi, Simona; Dalle Grave, Riccardo
Abstract : Introduction . Aim of this study was to compare the resting energy expenditure (REE) measured by the Douglas bag method with the REE estimated with the FitMate method, the Harris-Benedict equation, and the Müller et al. equation for individuals with BMI < 18.5 kg/m 2 in a severe group of underweight patients with anorexia nervosa (AN). Methods . 15 subjects with AN participated in the study. The Douglas bag method and the FitMate method were used to measure REE and the dual energy X-ray absorptiometry to assess body composition after one day of refeeding. Results . FitMate method and the Müller et al. equation gave an accurate REE estimation, while the Harris-Benedict equation overestimated the REE when compared with the Douglas bag method. Conclusion . The data support the use of the FitMate method and the Müller et al. equation, but not the Harris-Benedict equation, to estimate REE in AN patients after short-term refeeding.